2016
DOI: 10.17269/cjph.107.5366
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward holistic wellness, empowerment and self-determination for Indigenous peoples in Canada: Can traditional Indigenous health care practices increase ownership over health and health care decisions?

Abstract: OBJECTIVES: This study aimed to understand the role that traditional Indigenous health care practices can play in increasing individual-level self-determination over health care and improving health outcomes for urban Indigenous peoples in Canada.METHODS: This project took place in Vancouver, British Columbia and included the creation and delivery of holistic workshops to engage community members (n = 35) in learning about aspects of traditional health care practices. Short-term and intermediate outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 18 publications
2
63
0
Order By: Relevance
“…These findings parallel a recent study showing that support for and access to Indigenous healing practices in an urban setting increases empowerment and selfdetermination within healthcare relationships. 5 Indeed, it is well known that patients with chronic conditions have many strategies to become invested and activated in their own care. 20 The agency and understanding from this result in better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings parallel a recent study showing that support for and access to Indigenous healing practices in an urban setting increases empowerment and selfdetermination within healthcare relationships. 5 Indeed, it is well known that patients with chronic conditions have many strategies to become invested and activated in their own care. 20 The agency and understanding from this result in better health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Reintroducing Indigenous healing practices improved ownership over choices around, and access to, diverse health systems. 5 Further, cultural continuity, implying utilization of healing practices, guards against the development of diabetes 6 and the occurrence of suicide. 7 However, these approaches have not been broadly realized in western health systems that privilege biomedical approaches and western knowledge paradigms and models.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural engagement has been shown to be beneficial to the health and well-being of Indigenous people (Auger, Howell, & Gomes, 2016;Gone, 2011;Gone & Looking, 2011). However, government policies aimed at cultural extermination and assimilation have resulted in a tremendous loss of Indigenous knowledge, including end-of-life practices and ceremonies.…”
Section: Indigeneity In Urban Settlementsmentioning
confidence: 99%
“…Studies in several countries have already reported on the importance of incorporating such practices into institutional settings, as the need for this type of care is the right of health service users. 11,12 They also point out that such practices should guide state obligations regarding these populations. 11 Research shows that even though healthcare models take into account the peculiarities of the population, there is a tendency for their underutilization to the detriment of the reproduction of the curatorial medical-hegemonic model.…”
Section: Meaning Of Children Follow-up Consultations Among Mothersmentioning
confidence: 99%
“…10 Other countries have also been respecting popular knowledge in their established care models, as evidenced by research in Canada, England, South Africa, Kenya and Jordan; the use of traditional, complementary and alternative practices are highlighted as a right of the people and even fundamental in the care process and the adoption of health decisions. 11,12 Thus, professionals need to promote health care that prioritizes peculiarities and respects the culture of the people during GDM consultations in the quilombo communities. 9 Added to these issues is the unsatisfactory degree of adherence of children to GDM consultations with this problem being considered a challenge for health services.…”
Section: Introductionmentioning
confidence: 99%